Revisiting the Efficiency-Equity Trade-off: A Muli-objective Linear Problem combined with an extended Leontief Input Output - Model - Mikuláš Luptáčik; Bernhard Mahlberg (University of Economics in Bratislava, Department of Economic Policy, 2018)
In recent years there has been increasing interest in the question of how inequality affects economic growth. This growing interest has recently stimulated new theoretical aswell as empirical research. Some existing theoretical models propose income inequality is detrimental to growth, but alternative theoretical models point at inequality as a determinant furthering economic growth. The main goal of this paper is to obtain deeper insights into the so-called efficiency-equity trade-off. Recently the Stiglitz-Report (Stiglitz et al., 2010) revealed several limits of GDP as an indicator of economic performance and social progress and recommended to shift emphasis towards measuring people's well-being. Following this recommendation,we develop a new multiple criteria decision making model coupled with an extended Leontief input-output model taking into account the social dimension and obtain deeper insights into the so-called efficiency-equity trade-off.
Keywords: C61; C67; D63; I31; 330; Welfare beyond GDP; Utilitarian Social Welfare Function; Rawlsian Social Welfare Function